2006
DOI: 10.4049/jimmunol.177.7.4927
|View full text |Cite
|
Sign up to set email alerts
|

ICOS Deficiency Is Associated with a Severe Reduction of CXCR5+CD4 Germinal Center Th Cells

Abstract: ICOS is expressed on activated T cells and particularly on CXCR5+ follicular Th cells in germinal centers (GC). Its deletion leads to a profound deficiency in memory B cell formation and switched Ab response in humans. Here, we show that in ICOS-deficient patients the generation of GCs is severely disturbed, and the numbers of circulating CXCR5+CD45RO+ memory CD4 T cells are significantly reduced, indicating an essential role of ICOS in the differentiation of CXCR5+CD4 T cells. The GC-specific CD57+CXCR5+ subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
321
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(340 citation statements)
references
References 35 publications
14
321
1
1
Order By: Relevance
“…Defects have been found in the genes that encode for B cell antigen receptor associated complex (CD19, CD81, and CD21) (25 27), CD20 (28), inducible co-stimulator (ICOS) (29), and B cell activating factor receptor (BAFF-R) (30). Nevertheless, taken together, these defects account for less than 3% of patients (31).…”
Section: Genetics Of Cvidmentioning
confidence: 99%
“…Defects have been found in the genes that encode for B cell antigen receptor associated complex (CD19, CD81, and CD21) (25 27), CD20 (28), inducible co-stimulator (ICOS) (29), and B cell activating factor receptor (BAFF-R) (30). Nevertheless, taken together, these defects account for less than 3% of patients (31).…”
Section: Genetics Of Cvidmentioning
confidence: 99%
“…The patients deficient in ICOS and CD40L lack T FHC cells, whereas T FHC cells expressing ICOS are overrepresented in SLE and rheumatoid arthritis patients. 10,51,53 T FH CELLS AND IMMUNODEFICIENCY Immunodeficiency is a pathological condition where the immune response is compromised or absent. Defects in humoural immune response lead to the humoral immunodeficiencies, such as common variable immunodeficiency (CVID), X-linked hyper IgM syndrome (HIGM) and X-linked lymphoproliferative disease (XLP).…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…Consistently, ICOS-deficient mice were significantly depleted of CXCR5 1 T FH cells in the blood and lymphoid tissues, and that the lack of GC was associated with reduced numbers of CXCR5 1 T FH cells in B-cell follicles. 10 Furthermore, deletions of CD19 can also cause CVID, which is characterized by defective B-cell responses and lack of T FH cells. 59 Similar to these findings, individuals suffering from XLP and SAP-deficient mice also exhibit severely impaired B-cell responses with altered development and/or function of T FH cells.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in mice and humans, interruption of ICOS-ICOS-L interaction leads to impaired GC reaction, Ab class switch, and affinity maturation (13)(14)(15)(16). Recent findings suggested that these defects in humoral immune responses in ICOS-deficiency are due to the lack of T FH cells (17)(18)(19). Conversely, dysregulated overexpression of ICOS in sanroque mice causes a lupus-like autoimmune disease that is associated with an increased number of T FH cells, spontaneous GC reaction, and augmented IL-21 production (20)(21)(22).…”
Section: Cd28 ͉ Follicular B Helper T-cell ͉ Germinal Center ͉ Icos ͉mentioning
confidence: 99%